Description of a new species of Thevenetimyia (Diptera: Bombyliidae) from Madagascar, with a revised checklist of Madagascan bee fly fauna - Maass, Natalia; Larmore, Zachary; Bertone, Matthew A.; Trautwein, Michelle (Zootaxa, 2016)
Madagascar is an island known for its richness of endemic species, including flies. Only eight genera of bee flies (Bombyliidae), including 17 described species (the majority of which are in the subfamily Anthracinae), are known from Madagascar. Here we describe a new species of Bombyliidae from Madagascar, Thevenetimyia spinosavus Maass & Bertone sp. nov. This fly represents the first record of the genus Thevenetimyia from Madagascar and the second species recorded in the Afrotropical Region. A revised checklist of Bombyliidae in Madagascar is provided, along with an appendix of associated literature. The known bee fly species likely represent only a fraction of the true diversity on the island, which has been relatively well sampled through extensive Malaise trapping of flies in Madagascar over the past decade.